2016
DOI: 10.1002/2016jd025027
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation and surface energy budget over the largest high‐altitude saline lake on the Qinghai‐Tibet Plateau

Abstract: Interactions between lakes and the atmosphere at high altitudes are still poorly understood due to difficulty in accessibility of direct measurements. This is particularly true for the Qinghai‐Tibet Plateau (QTP), where approximately 50% of the lakes in China are located. Continuous direct measurements of the water flux and surface energy budget were made over the largest high‐altitude saline lake in China, Qinghai Lake on the northeastern QTP, using the eddy covariance method from 11 May 2013 to 10 May 2015. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
102
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(108 citation statements)
references
References 51 publications
6
102
0
Order By: Relevance
“…For the lake evaporation in the TP, prior studies have discussed the determination of pan coefficients. For example, the direct lake evaporation can be obtained from eddy covariance systems and large evaporation pans for Ngoring Lake (Li et al ., ), Yamdrok Yum Co (Yu et al ., ) and Lake Qinghai (Li et al ., ) in recent years. Ma et al .…”
Section: Discussionmentioning
confidence: 99%
“…For the lake evaporation in the TP, prior studies have discussed the determination of pan coefficients. For example, the direct lake evaporation can be obtained from eddy covariance systems and large evaporation pans for Ngoring Lake (Li et al ., ), Yamdrok Yum Co (Yu et al ., ) and Lake Qinghai (Li et al ., ) in recent years. Ma et al .…”
Section: Discussionmentioning
confidence: 99%
“…The time lag between the R n and LE over lakes is closely related to the WD; deeper lakes exhibit longer time lags. A lag of 5 months exists for Lake Superior in North America (mean depth: 148 m) (Blanken et al, ); one of 4–5 months exists over Nam Co in Tibet, China (mean depth: 40 m) (Lazhu et al, ); one of 2–3 months exists over Qinghai Lake in China (mean depth: 21 m) (Li et al, ); and a relatively short lag of up to 1 month exists over Sparkling Lake in the United States (mean depth: 10.9 m; Lenters et al, ). Wang et al () reported a lag of 1 month over Lake Taihu in China (mean depth: 1.9 m).…”
Section: Discussionmentioning
confidence: 99%
“…The high LE events were found over Poyang Lake during the lake‐covered period, which are mainly controlled by dry and cold air masses and continuous high wind speed, that promote turbulent exchanges via enhanced turbulent mixing thermally and mechanically (Li et al, ; H. Liu et al, ). The total high LE events accounted for over 20% of the annual LE at Qinghai Lake (Li et al, ) and the Ross Barnett Reservoir (H. Liu et al, ). However, the high LE events at Poyang Lake account for less than 10% of the annual LE, which is partly due to the limited lake‐covered periods and local‐scale synoptic weather events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations